Formulation and evaluation of herbal periodontal films of M. paradisiaca for periodontitis - A., Sanjana; S. H., Fiza; M. B., Divyashree (International Journal of Research in Medical Sciences, 2026)
Background: The present work aims to formulate and evaluate the herbal films of M. paradisiaca for periodontitis. Methods: Dental films were formulated using the ethanolic extract of M. paradisiaca by maceration with different polymers like HPMC K4M, Carbopol P71P. The ethanolic extract of M. Paradisiaca was subjected for the pre-formulations studies like preliminary phytochemical screening and the results showed the presence of flavonoids, carbohydrates, tannins, alkaloids, glycosides etc. Results: The films were prepared by using the solvent casting technique and the films were subjected for various evaluation studies like thickness, hardness, folding endurance, surface PH. Based on the physiochemical parameters the formulation F1 were considered to be the best. Conclusions: The present study reveals that both formulated films showed satisfactory film parameters. From the present investigation it can be concluded that film formulation incorporating banana peel extract can be a potential novel drug dosage form for treatment of Periodontitis.